Risk of deep vein thrombosis (DVT) in lower extremity after total knee arthroplasty (TKA) in patients over 60 years old - JianQing Gao; ZhiQiang Xue; JiYue Huang; Lei Chen; JianDong Yuan; Jing Li (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Purpose There is a significant risk of DVT after TKA. We aim to evaluate the potential risk factors for postoperative DVT in the lower extremities in TKA patients over 60 years of age and provide a reference for the effective prevention of DVT. Methods This retrospective study included patients older than 60 who underwent TKA surgery in our hospital from May 2015 to May 2022 and compared and analyzed patients' personal characteristics and clinical data with or without postoperative DVT. Logistic regression analysis was performed to determine the potential risk factors for DVT after TKA. The sensitivity and specificity of each risk factor in the diagnosis of DVT were compared by the ROC curve, and the value of this model in the diagnosis of DVT was further investigated using a multivariable combined diagnosis ROC curve model. Results A total of 661 patients over 60 who underwent TKA were included. Preoperative Hematocrit (HCT), platelet count, anesthesia mode, postoperative D-dimer, ESR, diabetes mellitus, and other aspects of the DVT group and non-DVT group were statistically significant after TKA (P < 0.05). Multivariate logistics regression analysis showed that preoperative HCT, anesthesia mode, and diabetes were independent risk factors for DVT in patients over 60 years old after TKA. Compared with the univariate ROC model, the multivariable combined ROC curve analysis model has a higher diagnostic value for the diagnosis of DVT. Conclusion DVT is common in patients over 60 years of age after TKA, and there is a multivariable influence on its pathogenesis. For patients over 60 with diabetes, neuraxial anesthesia is recommended for patients with high preoperative HCT levels, which may reduce the incidence of postoperative DVT.